NIMG-67. DISAPPEARING DOTS – TRANSIENT LATE ENHANCING LESIONS YEARS AFTER BRAIN RADIOTHERAPY. (9th November 2020) - Pan, Peter; Padilla, Oscar; Buss, Elizabeth; Elliston, Carl; Wang, Tony; Joanta-Gomez, Adela; Lignelli-Dipple, Angela; Iwamoto, Fabio; Kreisl, Teri; Welch, Mary; Haggiagi, Aya; Donovan, Laura; et al.
Abstract: BACKGROUND: Late-delayed radiation effects appear 6 months to years following radiotherapy. We characterize a species of small enhancing lesions in the late-delayed phase of post-radiotherapy that are distinct from the classic descriptions of radiation necrosis or pseudoprogression associated with mass effect and edema. These "disappearing dots" are small, do not exert mass effect nor edema, and spontaneously resolve. METHOD: We retrospectively describe a series of cases with "disappearing dots" following brain radiotherapy. RESULTS: There were 10 cases (4 men), median age 42 years (range 29-63). Diagnoses were glioblastoma (3); low grade astrocytoma, anaplastic astrocytoma, and anaplastic oligodendroglioma (2 each); and solitary fibrous tumor (1). All patients received 54-60 Gy (Gray) of external beam radiotherapy, except one (proton beam therapy to 60 cobalt Gray equivalent). Disappearing dots appeared at a median of 27 months (range 5-197) post-radiotherapy. Lesions were relatively small (~< 1 cm 3 ), peri-ventricular, and within the radiotherapy field. Most enlarged before resolving. Advanced MR imaging and fluorodeoxyglucose (FGD)-PET results were inconsistent. Lesions persisted a median of 8.5 months (range 1-49) before spontaneous resolution. All were asymptomatic. Biopsy in one case revealed treatment effects rather than recurrent tumor. CONCLUSIONS: Asymptomatic small periventricular enhancing lesions can develop and remit spontaneously, years following brain radiotherapy. Such disappearing dots should be part of the differential diagnosis along with tumor recurrence. of new enhancing lesions in the late-delayed phase post-radiotherapy.